The earl, the kings, and the chronicler Robert Earl of Gloucester and the reigns of Henry I and Stephen - Patterson, Robert B. ca. 20./21. Jh (Oxford scholarship online, 2019)
'The Earl, The Kings, And The Chronicler' is a full length biography of Robert (1088-1147), grandson of William the Conqueror and bastard eldest son of King Henry I of England. Robert could not succeed his father, but played a key role in the Anarchy against King Stephen, and had a lasting impact on British cultural and political history